Empirical evidence on factors conditioning the turning point of the public debt-growth relationship - Mindaugas Butkus; Diana Cibulskiene; Lina Garsviene; Janina Seputiene (Economies, 2021)
This paper contributes to the limited literature on the factors conditioning the turning point of the public debt-growth relationship. A decade after the global financial crisis, when the debt ratio in many countries was still above pre-crisis levels, the COVID-19 pandemic kagain increased the pressure on public finances. It revived the debate on the ability to promote economic recovery through debt-financed government expenditure. However, more intense government borrowing increases its costs and uncertainty about future taxation policy, thus potentially disturbing private consumption, investment, and economic growth. In this paper, we estimate the thresholds of indicators on which the expenditure multiplier depends, which may already imply a risk that public debt will dampen economic growth. We use a methodology of structural threshold regression to examine the varying effects that debt might have on growth using consumption, investment, taxes, and imports as threshold variables, as well as several other factors suggested by previous contributions. The applied methodology allows for the addressing of parameter heterogeneity and endogeneity to be accounted for at the same time. The main results suggest that a positive debt effect is more likely if the conditions for a high expenditure multiplier are met, that an increase in the public-debt-to-GDP ratio is not necessarily deleterious to growth if shares of private consumption and investment in GDP are high, while the tax-revenue-to-GDP ratio is low.
Keywords: 330; economic growth; expenditure multiplier; heterogeneity; public debt